Triple negative breast cancer in Moroccan women: clinicopathological and therapeutic study at the National Institute of Oncology - Rais Ghizlane; Raissouni Soundouss; Aitelhaj Meryem; Rais Fadoi; Naciri Sara; Khoyaali Siham; Abahssain Halima; Bensouda Youssef; Khannoussi Basma; Mrabti Hind; Errihani Hassan (BMC, 2012)
Abstract Background Triple-negative breast cancer (TNBC) is defined by the lack of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER-2) expression. This is an aggressive malignancy with a poor prognosis despite the high rates of response to chemotherapy. The aim of this study is to determine the clinicopathological, therapeutic features and outcomes associated with this type of breast cancer. Methods This is a retrospective study of confirmed triple negative breast cancer females collected at the National institute of oncology of Rabat in Morocco, between January 2007 and December 2008. Epidemiological, clinical, histological, therapeutic and evolutive data were analyzed. OS and DFS rates were estimated by Kaplan-Meier analysis. Results A total of one 152 patients with breast cancer, were identified as having triple-negative breast cancer (16,5%). The median age at diagnosis was 46 years. 130 patients (86%) had infiltrating ductal carcinoma and thirteen had medullar carcinoma (9%). 84 cases (55%) were grade III Scarff-Bloom-Richardson (SBR). 48 % had positive lymph nodes, and 5 % had distant metastases at diagnosis. According TNM staging, 12 patients (8%) had stage I, 90 patients (60%) had stage II and the 43(28%) had stage III. 145 patients received surgery. 41 (28%) had conservative surgery and 104 (72%) received radical mastectomy with axillary lymph nodes dissection. 14 patients with advanced tumors or inflammatory breast cancer have received neoadjuvant chemotherapy and four patients (28%) had complete pathologic response. From 131 patients how received adjuvant chemotherapy, 99 patients (75,5%) had Anthracycline based chemotherapy) and 27 patients (20,6%) had sequential Anthracycline and docetaxel,. Seven patients with metastatic disease received anthracycline-based regimen in the first line metastatic chemotherapy. The median follow-up time was 46 months (range 6,1 -60 months). Overall survival at 5 years for all patients was 76,5%. Conclusion These results suggest that most TNBC characteristics in Moroccan patients are in accordance with literature data, especially concerning young age at diagnosis high grade tumors, advanced stage at diagnosis, and short time to relapse. Although the high response rate to chemotherapy, the overall prognosis of this subset of tumors remains poor.